Serigrafi baskıda farklı baskı altı malzemeleri üzerine optimum mürekkep sarfiyatının tespiti - Akpolat, Cem (My University, 2025)
Serigrafi baskı, basılı mamül üretiminde kullanılan, çok farklı alanlara hizmet eden bir tekniktir. Çok farklı nitelikte mürekkep çeşidi, baskıaltı malzemesi, dokuma sıklığı kullanmaktadır. Her baskıaltı malzemesi farklı nitelikte kuruma çeşitli, mürekkep ihtiyacı ve bunun gibi değişen parametreler tercih etmektedir. Yapılan çalışmada, serigrafi baskı sisteminde çok farklı sayıda olan bu değişkenler içinden en uygun olanı saptamak için optimizasyon deneyleri yapılmıştır. Daha çok grafik endüstrisine hizmet veren düzgün yüzeyli baskıaltı malzemeleri seçilmiştir. Deneyler sırasında serigrafi baskının hedef kitlesine cevap verebilecek taş kağıt üzerinde basılabilirlik ve optimizasyon deneyleri yapıldı. Bu tezde kuşe etiket kağıt, taş kağıt, şeffaf PVC etiket ve mat-şeffaf PVC malzeme üzerindeki mürekkep sarfiyatı incelenmiştir. Taguchi metodu kullanılarak mürekkep sarfiyatı için optimize bir model üretilmiştir. Belirlenen parametreler içinde mürekkep çeşidi ve viskozitesinin, sarfiyat üzerindeki etkisi ortaya konmuştur. Ayrıca taş kağıdın su ve yağ direnci sebebiyle serigrafinin hizmet ettiği dış mekan baskılarına uygun olduğu, basılabilirlik testlerinde kuşe etiket kağıdı kadar başarılı olduğu sonucuna ulaşılmıştır. Taş kağıt, yapısının çoğu doğal mineraller olduğu için çevreye daha az zararlı ve PVC gibi petrol esaslı baskıaltı materyallerine alternatif olarak öne çıkmaktadır.

Screen printing is a technique used in the production of printed materials, serving a wide range of applications. Screen printing is a widely used technique in the service industry with a wide range of applications. It involves a variety of ink types, substrates, and mesh counts, each tailored to the specific requirements of the process. Every substrate possesses unique characteristics, such as drying behavior and ink consumption, leading to diverse process parameters. In this study, optimization experiments were conducted to identify the most suitable parameters among these numerous variables within the screen printing system. To better align with the needs of the graphic industry, smooth-surfaced substrates were selected. The experiments focused on the printability and optimization of stone paper, aiming to meet the expectations of the target audience of screen printing. This thesis examines ink consumption on coated stickers, stone paper, transparent PVC stickers, and matte-transparent PVC materials. Using the Taguchi method, an optimized model was developed to reduce ink consumption. Among the identified parameters, ink type and viscosity were found to have the most significant effect on ink usage. Furthermore, it was concluded that stone paper, due to its water and oil resistance, is highly suitable for outdoor printing applications commonly served by screen printing. Printability tests demonstrated that stone paper performs as well as coated paper stickers, making it a viable alternative for such applications. Stone paper is an alternative to petroleum-based substrates such as PVC, which is less harmful to the environment as most of its structure is made of natural minerals.
Determination of optimum ink consumption on different substrates in screen printing
Keywords: basılabilirlik; Basım endüstrisi; Basım makineleri ve gereçleri; baskıaltı malzemesi; ışık haslığı; lightfastness; printability; Printing industry; Printing machinery and supplies; printing substrate; rub resistance; serigrafi baskı; stone paper; sürtünme direnci screen printing; taş kağıt